Stature Estimation and Formulation of Regression Equation from Ear Anthropometry in Haryanvi Population - Monika Rathee; Jaswinder Kaur; Suresh Kanta Rathee (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Human beings are unique in number of physical characteristics like shape and form ofan individual. These characteristics are influenced by a wide range of racial, ecological, psychological,geographical, gender and biological variations. Human external ear is often overlooked during anthropometricmeasurements. The structure of human ear is so much variable that even two ears are different in sameindividual and it also varies according to age, sex, race and ethnic group.Authentic anthropometric data ofear for a particular population is necessary for designing of ear products for occupational environments, tofind out the age, sex and stature of an individual in that population. This data on ear measurements can alsobe helpful in forensic and medico-legal cases for personal identification of an individual. The main objectiveof the study is to find any relationship between ear parameters and stature and also to formulate regressionequation for estimation of stature in Haryanvi adult Jaats.Methods: The present study was conducted on 300 healthy Haryanvi Jaats (150 females and 150 males)aged 20 to 60 years. Measurements of ear length, ear breadth and stature were taken on each subject.Conclusion: Ear length and ear breadth are not significantly correlated with stature (p>0.05) in both thesexes except ear breadth which is significantly correlated with stature in males (p<0.05).The present study concluded that stature cannot be estimated from ear length and ear breadth in Haryanvipopulation.